Ethical Considerations in Clinical Biochemistry and Laboratory Medicine: A Discussion Based on ‘The Belmont Report’ (Bangladesh Journal of Bioethics, 2020)
With technical sophistication and innovation in the field of medical science, a considerable proportion of medical diagnosis now rely on laboratory analyses, which emphasises the crucial role of laboratory physicians in patient care. Sustaining high ethical standards remains crucial in both clinical biochemistry and laboratory medicine, and several ethical dilemmas are faced by laboratory physicians in day-to-day practice. In a low-resource country like Bangladesh, formal ethics education or ethical framework in laboratory practice is still absent; ethics has not received that much attention it this field. This paper has considered ethical issues encountered during the daily routine work of laboratory physicians and specially focused on the ethical issues encountered during the pre-analytical, analytical and post-analytical phases of laboratory medicine practice and discuss those issues in light of ‘The Belmont Report’ (1978) perspective. It is not intended to be a comprehensive one, rather it aims to complement existing guidelines and documents that are available in some institutions and to offer a framework for addressing ethical issues encountered in the practice of clinical biochemistry and laboratory medicine in Bangladesh.